Pengaruh Motivasi dan Disiplin Kerja Guru Terhadap Kinerja Guru - Heny Desi Soviana; Veithzal Rivai Zainal; Setyo Riyanto (Publikasi Indonesia, 2023)
Conditions in the field regarding teacher performance in private schools, namely kindergarten-elementary school MKD located in Cimahi city, show that there is a lack of motivation and many teachers are still not disciplined in attendance. This study was conducted with the aim of determining how the influence of work motivation and work discipline on teacher performance. The research method used is a quantitative method with sampling techniques using saturated sampling techniques where all members in the population are sampled, namely as many as 36 teachers. The results of the research obtained stated that teacher motivation and work discipline have a positive and significant effect on teacher performance, so it can be said that the higher the teacher's work motivation and work discipline, the better the teacher's performance.